Examining Turkish Adults' Recalled Experiences of Their Father's Presence - (:unkn) unknown (SAGE PUBLICATIONS INC, 2019)
The father plays an important role in child development, including during adolescence, in many cultures. To date, research on the impact of father presence (in a household/family) on father-child relationships has been limited, especially in Eastern cultures due to the overwhelming influence of traditional gender role attitudes. The purposes of this study are to record and compare descriptions (i.e., profiles) of the father's presence, and to investigate Turkish adults' reported experiences of their father's presence during their childhood. A sample of 401 participants completed a Turkish version of the Father's Presence Questionnaire. The resulting profiles and analyses of reports of the father's presence show that perceptions of the fathers' involvements with the participants and the participants' feelings about their fathers are strongly correlated with their reported father-mother relationships as well as the mother's support for the relationship with the father. The profiles of the male and female adult participants were quite distinct regarding recollections of physical closeness with the father because of the less frequent physical interactions between males and their fathers compared with females.
Keywords: fatherhood; father presence; father-child relationship; father-family relationship; gender and family; INVOLVEMENT; TRANSMISSION; FAMILY; IMPACT